PELAKSANAAN KEARSIPAN DI BAGIAN UMUM SEKRETARIAT DAERAH KOTA SURAKARTA - Aprilia Nur Arninasari; Hery Sawiji; Susantiningrum Susantiningrum (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2022)
The purpose of this study are to determine the implementation of archives in the General Section of the Regional Secretariat of Surakarta City. This study is a descriptive qualitative study employing a case study technique. The study was carried out in the Surakarta City Regional Secretariat's General Section. Purposive sampling was a technique for taking samples. Observation, interviewing, and document analysis were used to compile data. Check the accuracy of the data obtained through source and method triangulation. The data analysis technique included interactive model data analysis.The result of this study reveal that: 1) The implementation of archives in the General Section of the Surakarta City Regional Secretariat which uses an active dynamic archive management system which includes the creation stage such as receipt and recording of records, the using stage such as archive arrangement and archive storage, archive maintenance and caring, and depreciation stages such as moving archives that are already running quite well, 2) The implementation of archives in the General Section of the Regional Secretariat of Surakarta City is exist some problems like as lacking of human resources in the field of correspondences and lacking of archival supporting infrastructure, and 3) Conducting to solve some problems be found in the General Section of the Regional Secretariat of Surakarta City such as planning of increasing human resources and budgeting for facilities and infrastructure.